Membangun Generasi Z Anti Narkotika Perspketif Maqashid Syariah - Andriyani Andriyani; Hijriyana Safithri (AKM, 2024)
Drug abuse among adolescents is always increasing. This of course will affect the life of the nation, because the generation that is expected to develop the progress of a country, on the contrary, can cause damage to the country. Therefore, the next generation of the nation must be kept away from narcotics. One of the efforts to create an anti-narcotics generation is to serve Generation Z in order to provide them with an understanding of the dangers of narcotics. This service is focused on generation Z, namely someone born between 1996-2012, in this case students of SMK Negeri 3 Lubuk Linggau. The material for dedication is narcotics abuse in the perspective of maqasid sharia. The material was chosen because usually SMK students have little knowledge about religion. The service method is carried out by way of a seminar, namely the delivery of material, questions and answers and evaluation through quizzes. The results of the dedication concluded that students who previously did not know anything about maqashid sharia, now have little understanding of it. The most important thing is that they can understand the purpose of prohibiting narcotics abuse in the perspective of maqashid sharia.